Edukasi Gizi pada Kelompok Risiko Melahirkan Balita Stunting - Podojoyo Podojoyo; Yulianto Yulianto; Sartono Sartono; Ahmad Sadiq; Mardiana Mardiana (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2026)
Stunting is still one of the main public health problems in Indonesia because it has an impact on the quality of human resources in the future. The results of anthropometric measurements and consumption surveys on under five years at The Public Health Center of Seri Tanjung were obtained with a stunting prevalence of 31.1%, and underweight of 19.7%. Nutritional intake of toddlers is energy deficient (47.6%), and toddlers suffer from infectious diseases as much as 42.5%. From this data, preventive efforts need to be made to prevent an increase in the prevalence of stunting in the form of nutrition education in adolescents, pregnant women, lactating mothers and mothers under five. After nutrition education was given, there was an increase in the average value of knowledge compared to before the education was given. Thus, providing nutrition education is a treatment that helps to increase knowledge about nutritious food for both mothers and children.